Isolation Of Stigmasterol from the leaves of Kopsia Singapurensis RIDL - Lee Yean Shan, Ahmad Kartini, Awang Khalijah, Tan Siow Ping, Nafiah Mohd Azlan (N/A, 2012)
Isolation Of Stigmasterol from the leaves of Kopsia Singapurensis RIDL by Lee Yean Shan, Ahmad Kartini, Awang Khalijah, Tan Siow Ping, Nafiah Mohd Azlan,